Comparison of Scalar Magnetic Field Data of China Seismo-Electromagnetic Satellite and Swarm Bravo Satellite - Jianing, Zhang; Bingjun, Cheng; Yuqi, Tong; Yuanqing, Miao; Bin, Zhou; Andreas, Pollinger; Xinghong, Zhu; Yanyan, Yang; Xiaochen, Gou; Yiteng, Zhang; Jindong, Wang; Lei, Li; et al. (Frontiers in Earth Science, 2022)
Based on the in-orbit magnetic field data of China Seismo-Electromagnetic Satellite (CSES) and Swarm Bravo satellite, some researches on the data consistency comparison and cross calibration were carried out. The condition applied is that two satellites pass by in a relatively short period of time and through spatial location at a relatively close range, and different spatial-temporal scale standards were set, combined with Kp index to screen for geomagnetic quiet periods. Then with the help of CHAOS model, indirect analysis was realized. Furthermore, the difference between the in-orbit data and model value was visualized, and the phenomenon and possible reason of data variation with time and geomagnetic latitude variation were analyzed. These analysis results are displayed in this article, which may evaluate the reliability of the satellite magnetic field detection data and the consistency of multiple satellites detection results, and provide a methodological reference for doing similar evaluation and analysis subsequently.